INTRUSION DETECTION SYSTEMS USING BLOCKCHAIN TECHNOLOGY - Kizito Kekeli Dynne; P. Srivaramangai (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
As a result of the increasing frequency of cyber-attacks on all fronts, research towards more robust and flexible intrusion detection systems (IDS) are required to help combat and alleviate criminal attacks by threat actors. collaborative measures are proving to be a better form of IDS as compared to standard signature or anomaly IDS. Collaborative IDS however still face a fundamental trust challenge. ledger-based blockchain technology seeks to solve this problem using a Collaborative Intrusion Detection System (CIDS) incorporating blockchain technology to protect data integrity as well as securing accountability for all nodes in the network.